(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the current situation of injury among the people in two communes of Vu Thu district, Thai Binh province in 2024. Subjects and methods: Research conducted on the subjects are people in Minh Khai and Song Lang communes, Vu Thu district, Thai Binh province, with a total of 411 households (1452 people) participating. Results: The rate of injuries in the study area in 2024 was 8.9%. Traffic accidents are the most common type of injury (42.3%), followed by falling (23.8%) and labor accidents (20%). The main cause of injury is unintentional itself (63.1%). 87.7% of the first aid, of which 72.8% were given first aid within 30 minutes after the accident. The majority of injured individuals fully recovered (89.2%), while 10.8% left sequelae. Conclusion: The situation of injury accidents shows that this is still a big challenge for public health, requiring timely attention and intervention.